Composite versus single transportable carbohydrate solution enhances race and laboratory cycling performance - Rowlands, D. S.; Swift, M.; Ros, M.; Green, J. G. (Applied Physiology, Nutrition, and Metabolism, 2012)
When ingested at high rates (1.8-2.4 g/min) in concentrated solutions, carbohydrates absorbed by multiple (e.g., fructose and glucose) vs. single intestinal transporters can increase exogenous carbohydrate oxidation and endurance performance, but their effect when ingested at lower, more realistic, rates during intermittent high-intensity endurance competition and trials is unknown. Trained cyclists participated in two independent randomized crossover investigations comprising mountain-bike races (average 141 min; n = 10) and laboratory trials (94-min high-intensity intervals followed by 10 maximal sprints; n = 16). Solutions ingested during exercise contained electrolytes and fructose + maltodextrin or glucose + maltodextrin in 1:2 ratio ingested, on average, at 1.2 g carbohydrate/kg·h. Exertion, muscle fatigue, and gastrointestinal discomfort were recorded. Data were analysed using mixed models with gastrointestinal discomfort as a mechanism covariate; inferences were made against substantiveness thresholds (1.2% for performance) and standardized difference. The fructose-maltodextrin solution substantially reduced race time (-1.8%; 90% confidence interval = ±1.8%) and abdominal cramps (-8.1 on a 0-100 scale; ±6.6). After accounting for gastrointestinal discomfort, the effect of the fructose-maltodextrin solution on lap time was reduced (-1.1%; ±2.4%), suggesting that gastrointestinal discomfort explained part of the effect of fructose-maltodextrin on performance. In the laboratory, mean sprint power was enhanced (1.4%; ±0.8%) with fructose-maltodextrin, but the effect on peak power was unclear (0.7%; ±1.5%). Adjusting out gastrointestinal discomfort augmented the fructose-maltodextrin effect on mean (2.6%; ±1.9%) and peak (2.5%; ±3.0%) power. Ingestion of multiple transportable vs. single transportable carbohydrates enhanced mountain-bike race and high-intensity laboratory cycling performance, with inconsistent but not irreconcilable effects of gut discomfort as a possible mediating mechanism.